Future time perspective sebagai mediator pengaruh sikap pro-lingkungan terhadap adaptasi rumah tangga menghadapi perubahan iklim di Aceh - Riamanda, Irin (Fakultas Psikologi Universitas Hang Tuah, 2026)
Climate change requires adaptation at both policy and household levels. This study examines the link between future time perspective and household adaptation capacity. It also explores its indirect role connecting pro-environmental attitudes and adaptation capacity in Aceh. Using a correlational quantitative design with a simple mediation model, 307 urban households were recruited through convenience sampling. Data were collected using instruments measuring pro-environmental attitudes, future time perspective, and adaptation capacity, and analyzed with a bootstrap-based mediation test in JASP. Results show that pro-environmental attitudes do not directly affect household adaptation capacity, but future time perspective has a positive effect. The relationship between pro-environmental attitudes and future time perspective is not significant, but the indirect effect is small and supported by the bootstrap confidence interval (β = 0.039; 95% CI [0.005, 0.096]). These findings suggest that a future-oriented perspective may strengthen household readiness for climate change.